Challenges in Rolling out the Framework of Categories and Concepts of Tax Code of Ukraine in Terms of “Tax Liability” Categor - Vakaryuk, Lyudmyla; Babin, Igor (Silesian Journal of Legal Studies, 2017)
Tax liability is one of the primary taxation law categories. It was originally implemented by the Law of Ukraine “On Value Added Tax” and later spread to all specific legal types of tax by the Law of Ukraine “On the Procedure for Paying off Taxpayers’ Obligations to Budgets and State Trust Funds”. Academics are divided in their approach to the term “tax liability”, which has, in turn, affected the further development of this category in the tax legislation of Ukraine1. The systematisation of tax legislation and the adoption of the Tax Code of Ukraine led to a narrow use of this category and its partial substitution by other inadequate concepts. The result of such unjustified and inconsistent activities by the legislator increased the complication and extended the taxation-legal terminology and the contradictions between the General and Special Parts of the Tax Code of Ukraine. Therefore, the studies of the legal nature and the content of tax liability still remain relevant.